2023
DOI: 10.1071/ch22267
|View full text |Cite
|
Sign up to set email alerts
|

An autoantigen-ome from HS-Sultan B-Lymphoblasts offers a molecular map for investigating autoimmune sequelae of COVID-19

Abstract: To understand how COVID-19 may induce autoimmune diseases, we have been compiling an atlas of COVID autoantigens (autoAgs). Using dermatan sulfate (DS) affinity enrichment of autoantigenic proteins extracted from HS-Sultan lymphoblasts, we identified 362 DS-affinity proteins, of which at least 201 (56%) are confirmed autoAgs. Comparison with available multi-omic COVID data shows that 315 (87%) of the 362 proteins are affected in SARS-CoV-2 infection via altered expression, interaction with viral components, or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 212 publications
0
4
0
Order By: Relevance
“…Because different tissues or cells may give rise to distinct pools of autoAgs, we have been profiling autoAgs from multiple human tissues and cell types, including human lung fibroblast HFL1 cells, human lung epithelial-like A549 cells, and B-lymphoblast HS-Sultan cells. [1][2][3] In this study, we report an autoantigen-ome identified from human Jurkat T-lymphoblast cells.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Because different tissues or cells may give rise to distinct pools of autoAgs, we have been profiling autoAgs from multiple human tissues and cell types, including human lung fibroblast HFL1 cells, human lung epithelial-like A549 cells, and B-lymphoblast HS-Sultan cells. [1][2][3] In this study, we report an autoantigen-ome identified from human Jurkat T-lymphoblast cells.…”
Section: Introductionmentioning
confidence: 93%
“…Proteins eluted with 1.0 M NaCl possess the strongest DSaffinity and, strikingly, 10/11 (90.9%) are known autoAgs (Table 1), indicating that increasing affinity to DS increases the propensity of a protein to be an autoAg, consistent with our prior findings. [1][2][3][4][5][7][8][9] These include histones (H4, H2B Histone autoAbs are nearly always present in drug-induced systemic lupus erythematosus, and ribosomal P autoAbs are tested for to aid in the differential diagnosis of lupus patients with neuropsychiatric symptoms. C1QBP has been repeatedly identified as a putative autoAg in several of our prior studies, [1,2,7,8] and was recently confirmed as an autoAg in the neurodegenerative disorder primary openangle glaucoma.…”
Section: Autoantigen-ome Of Jurkat Cells Identified By Ds-affinitymentioning
confidence: 99%
See 2 more Smart Citations